Pengaruh Pemberian Jus Wortel pada Penderita Hipertensi di Posyandu Lansia Desa Montong Kabupaten Tuban - Dita Marta Sari; Dwi Kurnia PS; Ahmad David Royyifi Arifin (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Hypertension is a medical condition characterized by systolic blood pressure ≥140 mmHg and diastolic blood pressure ≥90 mmHg, which are at risk of causing various complications. One of the efforts to control hypertension is through non-pharmacological therapies such as a healthy diet, including the consumption of carrot juice. This study aims to determine the difference in blood pressure reduction in elderly people with hypertension who are given carrot juice at the Posyandu Elderly in Montong Village, Tuban Regency. The study uses a quantitative approach with an experimental quasy design and a "Two Group Pre-test and Post-test Design" design. The sample consisted of 18 respondents who were selected through purposive sampling techniques. Data collection was carried out using a needle sphygmomanometer and observation sheet, then analyzed with the Paired T-Test and the Independent Sample T-Test. The results showed that the group given carrot juice experienced a significant decrease in blood pressure, with mean systolic values from 162.3 mmHg to 145.5 mmHg and diastolic from 90.0 mmHg to 81.67 mmHg. These findings show a difference in blood pressure before and after the carrot juice intervention. The conclusion of this study is that carrot juice has the potential to be an effective alternative to non-pharmacological therapy in lowering blood pressure in the elderly with hypertension. This research is expected to be a reference for health workers in the development of local food-based interventions for hypertension control.